BOOK REVIEW: THE 33 STRATEGIES OF WAR - Muhammad Umar Pervaiz (Margalla Papers, 2022)
The 33 Strategies of War showcases a guide to understanding everyday life’s social conduct conversant to military principles in war. Robert Greene is an American author who wrote several books on strategy. The book, in hand, contains 33 chapters divided into five parts. It accounts for discourses and examples of offensive and defensive strategies within various conditions and by people like Sun Tzu, Napoleon Bonaparte and Alexander.